Concomitant behavior of arsenic and selenium from the karst infillings materials of the fractured carbonate Dogger Aquifer (Hydrogeological Experimental Site, Poitiers, France). (July 2021) - Mhanna, R.; Naveau, A.; Bueno, M.; Shmeit, M.; Ismail, F.; Fontaine, C.; Porel, G.; Bassil, J.; Caner, L.
Abstract: Petrographic and mineralogical analyses combined with sequential extractions and leaching experiments as a function of pH were performed on black clayey sediments fulfilling karsts in the Hydrogeological Experimental Site (HES) of Poitiers (France) to investigate the behavior of arsenic and selenium in a fractured limestone aquifer. Sequential extractions showed that arsenic is mainly associated with pyrite (about 35%) and secondary iron oxyhydroxides (around 13%), along with a substantial exchangeable fraction (about 13%). The soluble fraction and the fraction associated to organic matter are ∼2% and ∼5%, respectively. The distribution of selenium is mainly pyritic (around 39%) or associated with organic matter (about 18%). Its association to secondary iron oxyhydroxides minerals is low (around 2%), whereas its soluble fraction is around 5%. SEM analyses revealed the presence of arsenic "hot spots" into euhedral pyrite crystals surrounded by a halo of iron oxyhydroxides resulting from their alteration, and both are enriched with arsenic. Selenium has a similar pyritic origin but after alteration, it is predominantly associated with organic matter. Despite different distributions, the leaching experiment as a function of pH showed that the mobilization of arsenic and selenium overlapped below pH 2 and above pH 8. The main differences were observed between pH 2 and 8 with a plateau at 5% of released selenium, whereas the amount of mobilized arsenic continuously decreased. The pH-dependence of both elements is attributed to the partial dissolution of pyrite in acidic conditions combined with desorption processes at higher pH values. Highlights: Clayey karst-infillings of the mid-Jurassic aquifer are geogenic sources of Se in the HES of Poitiers. Pyritic minerals were initially the main carrier of As and Se in the clayey materials. After pyrite oxidation, As was primarily associated with iron oxyhydroxides and Se was associated with OM. In acidic and basic conditions, their release is controlled by partial dissolution of the carrier phases and desorption processes, respectively. At circumneutral pH, As and Se exhibit different behaviors, with a higher release of Se than As.